1961
DOI: 10.1093/oxfordjournals.aje.a120219
|View full text |Cite
|
Sign up to set email alerts
|

Illness and Microbial Experiences of Nursery Children at Junior Village1

Abstract: Engler, J. I.; Parrott, R. H.; and Huebner, R. J. Pharyngoconjunctival Fever-Epidemiological Studies of a Recently Recognized Disease Entity. J.A.M.A. 157:1083-1092 (Mar. 26), 1955. 7. Jawetz, E.; Thygeson, P.; Hanna, L.; Nicholas, A.; and Kimura, S. J. The Etiology of Epidemic Kerato-conjunctivitis. Am. J. Ophth. 43:79-83 (Apr.), 1957. 8. Bell, J. A.; Huebner, R. J.; Rosen, L.; Rowe, W. P.; Cole, R. M.; Mastrota, F. M.; Floyd, T. M.; Chanock, R. M.; and Shvedoff, R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1962
1962
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Todas las muestras de adenovirus no entérico (AdNE) se encaminaron para la vía clásica de identificación viral, o 15 sea, la inoculación en células HEp-2 . Se realizó la inoculación de 0.2 mL de la muestra de suspensión fecal en la proporción de 1:8, con AdNEs, en tubos de poliestireno con células HEp-2 en monolayer, mantenidas con 1 mL (en cada tubo) de Medio Mínimo de Mantenimiento, el que contenía solución de sales balanceadas (BSS), bicarbonato de sodio, sales de "Hanks", L-glutamina, aminoácidos no esenciales y esenciales, vitaminas, coenzimas, hormonas, ácidos nucleicos y derivados y 5% de suero bovino fetal.…”
Section: Técnicas Empleadasunclassified
“…Todas las muestras de adenovirus no entérico (AdNE) se encaminaron para la vía clásica de identificación viral, o 15 sea, la inoculación en células HEp-2 . Se realizó la inoculación de 0.2 mL de la muestra de suspensión fecal en la proporción de 1:8, con AdNEs, en tubos de poliestireno con células HEp-2 en monolayer, mantenidas con 1 mL (en cada tubo) de Medio Mínimo de Mantenimiento, el que contenía solución de sales balanceadas (BSS), bicarbonato de sodio, sales de "Hanks", L-glutamina, aminoácidos no esenciales y esenciales, vitaminas, coenzimas, hormonas, ácidos nucleicos y derivados y 5% de suero bovino fetal.…”
Section: Técnicas Empleadasunclassified
“…Report, 1965;Poole & Tobin, 1973), and in the U.S.A. by Glezen et al (1971) and Maletsky et al (1971). Some surveys have also been undertaken in nurseries and schools (Bell et al 1961;Pereira, Andrews & Gardner, 1967;Beem 1969;and Loda, Glezen & Clyde, 1972). Much of this work has been reviewed by Channock & Parrott (1965), by Miller (1968) and by Gardner (1968).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys for serum antibodies to type 3 carried out in various parts of the United States, Western Europe, Russia, Japan, Australia, and Formosa indicated that 40-50 per cent of children and 50-70 per cent or more of adults had neutralizing antibodies to type 3. [33][34][35][36][37][38][39][40][41][42][43][44] In the Washington, D. C., area where contemporary serologic surveys confirm a high prevalence for neutralizing antibodies to type 3,1 45 we have evidence that this high prevalence may be the result of relatively recent events. A survey of sera taken between 1950 and 1953 from the same population showed that only 20 per cent of the children and adults (to age 35) had neutralizing antibodies to type 3.…”
mentioning
confidence: 99%